Pemanfaatan TIK dan Akses Terhadap Kebutuhan KB Yang Tidak Terpenuhi - Maghfirah, Maghfirah; Samosir, Omas Bulan; Djutaharta, Triasih (Jurnal Ekonomi Kependudukan dan Keluarga, 2024)
The achievement of unmet need for family planning in the last two years has decreased from 14,7 percent in 2022 to 11,5 percent in 2023. However, that rate is still high because 2024 RPJMN target of unmet need for FP in Indonesia is 7,4 percent. The policies made by the government to reduce unmet need for FP are utilizing ICT and improving access to family planning services. Thus, this research aims to study the relationship between utilizing ICT and access with unmet need for FP in Indonesia. Based on data from 2017 IDHS, the analytical method used in this research are binary and multinomial logistic regression. The results show that the variable of ICT’s devices has a negative relationship with total unmet need for FP, for spacing, and limiting births. Internet has a positive relationship with total unmet need for FP and for spacing births, but negative relationship with unmet need for limiting births. Access to family planning services has a negative relationship with total unmet need for FP and for limiting births. So, it can be concluded that reducing the womens’s opportunities to have unmet need for FP can be done by utilizing ICT and access to FP services.